Molecular mechanism of gallium nitrate in inhibiting bacterial biofilm formation through pykF modulation - Xiaofeng Zhang; Junjie Dong; Bing Wang; Lingqiang Chen; Zhiqiang Gong; Jin Yang; Guizhao Shu; Qi Ning (PLoS ONE, 2026)
Purpose Gallium nitrate, a non-redox analog of iron (III), suppresses bacterial biofilms and virulence within the framework of bacterial regulation. This study investigates the molecular mechanisms and regulatory pathways through which gallium nitrate modulates bacterial activity and function. Methods The antimicrobial properties of gallium nitrate, its effects on bacterial biofilms, and gallium-responsive signaling pathways were assessed. Observation of marked upregulation of pyruvate kinase ( pykF ) expression following gallium nitrate exposure prompted in vitro and in vivo experiments to examine how gallium influences the expression, enzymatic activity, and functional role of bacterial pykF . Results Crystal violet staining, XTT assay, confocal laser scanning microscopy, and scanning electron microscopy consistently indicated that gallium nitrate suppressed bacterial biofilm formation and metabolic activity. Transcriptomic profiling and subsequent validation analyses further suggested a strong association between pykF and gallium-mediated antibacterial effects. Both in vitro and in vivo experiments revealed that pykF knockout significantly enhanced bacterial survival and biofilm formation. Conclusion Gallium nitrate modulates bacterial biofilm development and virulence, with its antimicrobial effect largely dependent on pykF upregulation. Concurrent therapeutic targeting of both pykF and gallium may provide a more effective strategy against persistent biofilm-associated infections. This work also establishes a mechanistic basis for clinical approaches aimed at reducing biofilm formation and limiting device-related infections.